Railway Ecology 2017
DOI: 10.1007/978-3-319-57496-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Monitor and Mitigate Wildlife Mortality in Railways

Abstract: Recording wildlife mortality on railways is challenging as they have narrow corridors and lower accessibility. To improve mitigation measures, surveys must be systematic and their frequency depending on the targeted species traits and biology. To obtain unbiased estimates in diverse contexts, the data should be corrected using mortality estimators. Mitigation measures must avoid that animals remain on the tracks, as trains cannot be instantly stopped. Box culverts, amphibian tunnels, and under-or overpasses al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 43 publications
(123 reference statements)
0
30
0
15
Order By: Relevance
“…For each section, we determined the number of collisions per year and divided by the length of each section to derive a collision rate (collisions·km −1 ·yr −1 ; as recommended by Carvalho et al. ) reported on both the highway and the railway for the years before and after mitigation. We did not include in our rate estimate measures of traffic volume, which were only available on the highway (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For each section, we determined the number of collisions per year and divided by the length of each section to derive a collision rate (collisions·km −1 ·yr −1 ; as recommended by Carvalho et al. ) reported on both the highway and the railway for the years before and after mitigation. We did not include in our rate estimate measures of traffic volume, which were only available on the highway (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Birds may use linear structures as breeding habitat due to their lower predatory pressure, higher temperature and larger number of food items, including road-killed ones (Mumme et al 2000; Morelli 2013; Morelli et al 2014; Heske 2015; but see Vierling (2000) which revealed sink effect of roadside ditches). Despite a lot of casualties (Carvalho et al 2017; Godinho et al 2017a; Lucas et al 2017; Murias et al 2017; Santos et al 2017), some animal groups such as raptors and scavengers may be highly dependent on road habitats as sources of food (Benítez-López et al 2010; Coleman and Fraser 1989). Linear structures change local abiotic conditions, leading to the emergence of strong environmental gradients that may increase the availability of niches and thus increase species diversity (Amarasekare 2003; Nord and Forslund 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, camouflage in ecosystems used by humans is likely most effective for species that blend-in with elevated structure, both natural and man-made. Indeed, camouflage and freeze responses among ground-dwelling species likely provide little protection from agricultural, landscaping, and transportation practices, each presenting lethal risk (Trombulak & Frissell, 2000; Kirk, Lindsay & Brook, 2011; Carvalho et al, 2017). For many species, humans present unnatural conditions and perturbations that heighten risk (Cushman, 2006; Wong & Candolin, 2015; Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%